2014
DOI: 10.1007/s00601-014-0922-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oblateness, Radiation and a Circular Cluster of Material Points on the Stability of Equilibrium Points in the Restricted Four-Body Problem

Abstract: Within the framework of restricted four-body problem, we study the motion of an infinitesimal mass by assuming that the primaries of the system are radiating-oblate spheroids surrounded by a circular cluster of material points. In our model, we assume that the two masses of the primaries m 2 and m 3 are equal to µ and the mass m 1 is 1 − 2µ. By using numerical approach, we have obtained the equilibrium points and examined their linear stability. The effect of potential created by the circular cluster and oblat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Recently, the oblateness coefficient [2], radiation pressure force [3], PoyntingRobertson drag [4], and other perturbing effects have been taken into consideration during the mathematical modeling for the RFBP. However, mathematically, based on the equation of motion, we still can classify these models into two types, the autonomous type and the non-autonomous type.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the oblateness coefficient [2], radiation pressure force [3], PoyntingRobertson drag [4], and other perturbing effects have been taken into consideration during the mathematical modeling for the RFBP. However, mathematically, based on the equation of motion, we still can classify these models into two types, the autonomous type and the non-autonomous type.…”
Section: Introductionmentioning
confidence: 99%
“…And in the third and last case, he has taken two of the primaries as oblate body and all the three primaries are source of radiation pressure. Falaye [16] investigated the stability of the equilibrium points in the restricted four-body problem under the effects of oblateness and solar radiation pressure and found that these equilibrium points are unstable. Arribas et al [22] investigated the equilibria of the symmetric collinear restricted four-body problem where primaries are placed in a collinear central configuration with both masses and radiation pressure of the peripheral bodies are equal.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the presence of oblateness coefficient and various values of Jacobi constant expanded the stability regions of the equilibrium points. Falaye in [23] investigated the stability of equilibrium points in the circular restricted four-body problem with the effect of oblateness, radiation, and a circular cluster of material points. After considering two equal masses, he obtained that all the equilibrium points are unstable.…”
Section: Introductionmentioning
confidence: 99%